USING BIG DATA IN AUDITING: OPPORTUNITIES AND CHALLENGES IN ENHANCING THE EFFECTIVENESS OF FINANCIAL AUDITING - Ali Abdulkareem Hadi (Journal of Economic and Economic Policy, 2026)
Objective: This research aims to assess the impact of big data on enhancing the effectiveness of financial auditing, with a particular focus on the challenges and opportunities facing regulatory bodies and accounting institutions in the government sector. The research highlights its importance in light of the research gap resulting from the concentration of most leading academic studies on the private sector context. Method: The research relied on an analytical approach to analyze the conceptual framework and global trends in the use of big data in auditing, and also used an applied/descriptive approach (the actual applied approach is mentioned here: e.g., case study or questionnaire analysis) to study the target sample in Iraq. Results:The main findings showed that the use of big data significantly contributes to improving the quality and efficiency of financial auditing by enabling auditors to conduct a comprehensive analysis of all transactions (continuous auditing) rather than relying on samples, thereby enhancing the ability of regulatory agencies to proactively detect risks and fraud. However, the results indicated an essential structural and technical problems, notably on the outdated infrastructure and the dire need for training human personnel. There is also the need to protect government’s sensitive data as it will be integrated into big technology. Novelty: The study commends that regulatory bodies should develop a dynamic governance model that will balance the maximum chances provided by the big data in consonance with cybersecurity demands. It also suggests the adoption of AI-inclined analytic audit model to improve the efficacy of financial procedure.